Experts' consensus on intraoperative radiotherapy for pancreatic cancer. (1st May 2019) - Li, Yexiong; Feng, Qinfu; Jin, Jing; Shi, Susheng; Zhang, Zhihui; Che, Xu; Zhang, Jianwei; Chen, Yingtai; Wu, Xiuhong; Chen, Rufu; Li, Shengping; Wang, Jing; et al.
Abstract: Pancreatic cancer (PC), one of the most lethal malignancies, accounts for 8%–10% of digestive system cancers, and the incidence is increasing. Surgery, chemotherapy, and radiotherapy have been the main treatment methods but are not very effective. However, only 20% of patients have the opportunity to undergo surgical operation. Approximately 30–40% of patients present with locally advanced, unresectable pancreatic cancer because of invasion of mesenteric vessels or adjacent organs. The first patient with unresectable pancreatic cancer was treated with Intraoperative radiotherapy (IORT) in 1959 [1]. Since then, new surgical and radiotherapeutic techniques have been developed, clinical trials have provided new evidence, and intriguing long-term effects have emerged from global metadatabases. IORT has the advantages of more accurate target, better local control rate, less complications, longer survival time and better life quality. During the past decade, IORT has been applied in some hospitals in the world, but there is little agreement on technical details and standards. A guidelines of IORT in pancreatic cancer is therefore necessary and timely. To develop standardized criteria for the application of IORT in pancreatic cancer, the experts from China to discuss treatment methods and arrive at a consensus on the indications, contraindications, and preferred techniques of IORT in pancreatic cancer. This detailed and agreed technical description of IORT may have implications on training, assessment, quality control, and future research.